Darwinian Evolution of Prions in Cell Culture - Li, Jiali; Browning, Shawn; Mahal, Sukhvir P; Oelschlegel, Anja M; Weissmann, Charles (Science (American Association for the Advancement of Science), 2010)
Prions are infectious proteins consisting mainly of PrPSc, a β sheet-rich conformer of the normal host protein PrPC, and occur in different strains. Strain identity is thought to be encoded by PrPSc conformation. We found that biologically cloned prion populations gradually became heterogeneous by accumulating "mutants," and selective pressures resulted in the emergence of different mutants as major constituents of the evolving population. Thus, when transferred from brain to cultured cells, "cell-adapted" prions outcompeted their "brain-adapted" counterparts, and the opposite occurred when prions were returned from cells to brain. Similarly, the inhibitor swainsonine selected for a resistant substrain, whereas, in its absence, the susceptible substrain outgrew its resistant counterpart. Prions, albeit devoid of a nucleic acid genome, are thus subject to mutation and selective amplification.